URBAN ENVIRONMENTAL DISASTER MITIGATION MODEL: INSIGHTS FROM AL-ANWAR MODERN ISLAMIC BOARDING SCHOOL, PACITAN - Risma Dwi Arisona; Sugeng Utaya; Budi Handoyo; Indriyani Rachman; Fumitoshi Murae; Siska Mandalia (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Aim: This study aimed to describe the Urban Environmental Disaster Mitigation Model at Al-Anwar Modern Islamic Boarding School in Pacitan Regency, with a particular focus on earthquake and tsunami mitigation strategies. Methodology and results: The research employed a qualitative case study approach. Primary data were collected through in-depth interviews, observations, and questionnaires. Data analysis was conducted using the Miles and Huberman model, with source triangulation employed to ensure data validity. The Urban Environmental Disaster Mitigation Model at Al-Anwar Modern Islamic Boarding School integrates disaster preparedness in educational and urban contexts. Supported by technology, policies, simulations, and SPAB program integration, it enhances risk assessment, evacuation planning, and resource mobilization, fostering technical, cognitive, and moral capacities. The model is replicable for coastal and seismic regions. Conclusion, significance and impact study: The findings show that the Urban Environmental Disaster Mitigation Model at Al-Anwar Modern Islamic Boarding School represents a comprehensive approach to preparedness by integrating disaster mitigation, environmental awareness, and technological innovation within an urban educational setting. Disaster knowledge, regular simulations, and the use of GIS, AR, and digital platforms have enhanced community readiness, while institutional commitment through policies and structured coordination ensures sustainability. The significance of this study lies in demonstrating how education can function as both a learning domain and a resilience hub, equipping students with technical, cognitive, and moral capacities to face earthquake and tsunami risks. Its impact extends beyond the school through community partnerships, resource mobilization, and replicable strategies adaptable to other coastal and seismic regions. Ultimately, the model fosters sustainable urban disaster risk reduction by embedding resilience into both institutional practices and educational culture.